LINGUISTIC FEATURES OF COMPLEX CONSTRUCTIONS IN ENGLISH AND UZBEK TEXTS (Ustozlar uchun, 2025)
This article investigates the linguistic features of complex constructions in English and Uzbek texts, highlighting syntactic and semantic distinctions and parallels. Drawing on corpus data and syntactic theory, the study explores how complex sentences are structured in both languages, focusing on subordination, coordination, relative clauses, and non-finite verb constructions. The findings reveal notable cross-linguistic similarities in the use of subordinate clauses for elaboration and distinction in typological behavior—especially in terms of word order, clause embedding, and nominalization strategies. The paper concludes by emphasizing the implications for translation studies, language teaching, and syntactic theory.